Distribuição de competência no que tange ao licenciamento ambiental - Silva, Pierry Novais (2007)
Environmental law aims to mitigate the degradation of the environment in light of man s necessity concerning the use of environmental resources. Therefore, we should comply with the balance of human beings needs in the development of all their faculties without endangering current and future generations. To reach this objective, Law rules man s operation related to the environment in a preventive and repressive way. Repressively, through the penalty imposition in light of the detection of some environmental damage. Preventively, through the inspection by the available instruments identified in the legal system. Environmental licensing is one of these preventive instruments. It is internationally provisioned in the declaration of principles of the United Nations conference about the environment, held in Stockholm, in 1972, and stands on legal grounds in the national legal structure, being set forth in the Act nr. 6.938/81 which deals with national politics in the environment accepted by the Federal Constitution acted in 1988. Notwithstanding its legal provision, it has been a lot difficult to carry out the environmental licensing. Brazil is structured trough the choice of the Federal State described in provisions 1 and 18 of the Constitution. The Federal State is known by the autonomy of its federative entities. According to this structure, it is important to distribute jurisdiction in order to avoid possible conflicts. Responsible for this balance, the Constitution establishes in provision 23, the operation among all entities; that s to say, they can all use its authority to monitor the environment. However, there is a series of questioning concerning what can be considered joint monitoring. Doctrine and case law constantly change their position. In certain occasions, they point to the individual performance of the entities based on the interest primacy; in others, they turn to the joint operation or even the connected operation, where all have to respond individually for the monitoring. The problem, therefore, lies on determining which entity has jurisdiction to license an enterprise. That is what this dissertation is about